PENEGAKAN HUKUM YANG BERORIENTASI PADA KEBERLANJUTAN SUMBER DAYA IKAN - Rochmani Rochmani (Jurnal Media Hukum, 2014)
Area  of  Indonesia  consists of  80% water, which  contains  abundance  of  potential  fish  resources,  Those  fish resources  should  be  utilized  for  as much  as  prosperity  and welfare  for  Indonesian.  In  fact,  fish  resourceshaven’t enhanced the  living  standard, which  is  sustainable and equitable.  Issues on fisheries come up such as exaggeration  of  fishing,  theft  fish,  illegal  fishing  activities  and  the  use  of  fish  resources  that  exceeding  thegeneration of fish  itself. That  circumstance will  cause harm  for  the state,  the fishermen, as well as people  in general.  The  use  of  tools  that  harm  the  nature will  cause  the  decrease  of  fish  resources  and  threat  thesustainability  of  fish  resources.  The  aim  of  writing  this  article  is  to  analyze  law  enforcement  related  to  the sustainability of fish  resources and the sustainability of  fish  resources, viewed from  the perspective of  justice.As the result of  the study,  law enforcement to protect the  fish resources generally has not given attention  to the  sustainability of  fish  resources,  therefore  fishermen  still  use  unfriendly  tools  to  catch  the  fishes.  Thoseunfriendly  tools will  cause  the  occurrence  of  over-fishing  and will  impact  to  the  environmental  damages. Those  kinds of  things will destruct  the  fishes,  therefore  the  quantity  of  fish will  have deteriorated and evencould  be  extinct.  Those  environmental  damages would  suffer  the  present generation  as well  as  the  next generation  since  they  couldn’t  consume  fish which  is  very  essential  for  the  growth  of  the human body  anderadicate  the job for the people as the fishermen. The present generation will be sinful if the next generation will get  the  impact of what  the present generation done.  In order  to  reduce more over-fishing activities and the  distrust  of  the  fish habitat  it  needs  the  law  enforcement, which  is oriented  to  the  sustainability of  fish resources.  The  sustainability  of  fishery  resources  couldn’t maintain  its  existence,  this  could  be  seen  as  the symbol  of  environmental  damages.  In  this  case,  the  law  also  needs  to make  integration  of  fish  resources sustainability to be processed so that  it will  result output  law enforcement which is oriented to  fish resourcessustainability.  As  a  conclusion,  in  law  enforcement  oriented  to  fish  resources  sustainability,  it  needs  to  be thought by the lawmaker to embed that the law should contain  idea or concept about justice,  legal certainty,the significance of fish resources and the implementation of the law itself. In the fish resources utilization and law enforcements, it needs to pay attention to the justice principle; intergenerational equity; intergenerational equity;  precautionary;  conservation  of  biological  diversity;  conservation  of  biological  diversity.